How Matthias Corvinus’ Bombards Captured Głogów in 1488 - Strzyż, Piotr (City and War, 2022)
Sieges in the Middle Ages were always a difficult logistical undertaking. The most serious problems were faced during sieges of such places as fortified towns or especially large castles. In such cases, a basic difficulty was posed by a need to organise a tight blockade of the selected place, in order to cut it off from any communication with the external world. Among many known sieges in the 15th century, the siege of Głogów in 1488 stands out, carried out by Hungarian troops. The hostilities lasted from 19th May to November 1488, which was almost a half of the year. The Hungarian troops were equipped with numerous pieces of artillery, including three large bombards from Wrocław, Świdnica and Legnica. These cannons inflicted considerable damage in the town during the siege. However, two of these burst. The town surrendered only after the stores of food had run out, and not due to bombardment. The course of event at Głogów demonstrates that during sieges of large centres with the use of the heaviest artillery in the 15th century it was difficult to achieve measurable success.